A GA-Based Approach to Hide Sensitive High Utility Itemsets. (3rd March 2014) - Lin, Chun-Wei; Hong, Tzung-Pei; Wong, Jia-Wei; Lan, Guo-Cheng; Lin, Wen-Yang
Abstract : A GA-based privacy preserving utility mining method is proposed to find appropriate transactions to be inserted into the database for hiding sensitive high utility itemsets. It maintains the low information loss while providing information to the data demanders and protects the high-risk information in the database. A flexible evaluation function with three factors is designed in the proposed approach to evaluate whether the processed transactions are required to be inserted. Three different weights are, respectively, assigned to the three factors according to users. Moreover, the downward closure property and the prelarge concept are adopted in the proposed approach to reduce the cost of rescanning database, thus speeding up the evaluation process of chromosomes.